2005
DOI: 10.1016/j.jvs.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Axillary-axillary interarterial chest loop conduit as an alternative for chronic hemodialysis access

Abstract: This short-term initial study showed that the AA IA loop access could be implanted with acceptable perioperative morbidity and with an excellent secondary patency rate. Further follow-up is necessary to determine the long-term complication rate and to allow more reasonable comparison with other methods of access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…23,24 Likewise, interarterial loops were not used because of their theoretical risks of ischemia and distal embolization. Zanow 25 and Bunger 20 reported this last complication in 5% and 3.2% of patients with an interarterial axillary-axillary loop for hemodialysis, respectively. To the best of our knowledge, the feasibility of arteriovenous brachial-brachial fistulas was not evaluated in chronic hemodialysis patients who had undergone one or more earlier attempts at surgical vascular access.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 Likewise, interarterial loops were not used because of their theoretical risks of ischemia and distal embolization. Zanow 25 and Bunger 20 reported this last complication in 5% and 3.2% of patients with an interarterial axillary-axillary loop for hemodialysis, respectively. To the best of our knowledge, the feasibility of arteriovenous brachial-brachial fistulas was not evaluated in chronic hemodialysis patients who had undergone one or more earlier attempts at surgical vascular access.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 The arterio-arterial grafts on thigh were also described well previously, but thrombosis rate of the femoro-inguinal arterioarterial prosthetic loop was high. 11,12 In the present study, the demographic character of the patients showed the mean patient age was 58±13 years; 60% were women. Comorbid conditions included diabetes mellitus (66.7%), coronary heart diseases (60%), hyperlipidemia (53.3%).…”
Section: Discussionmentioning
confidence: 45%
“…There are other upper limb options such as the interarterial axillary-axillary graft of which there is a case series with primary and secondary patency of 90% and 93% at six months. However, these patients had completely exhausted venous options, and thus the risks of an artery-to-artery graft were worthwhile [17]. A variety of lower limb procedures have been described and use of the saphenous vein as a conduit has rather lost favour due to the high rates of failure and need for further intervention [1822].…”
Section: Discussionmentioning
confidence: 99%